Does teaming obscure low performance? Exploring the temporal effects of team performance diversity - Rubino, C.; Avery, D. R.; Volpone, S. D.; Ford, L. (Human Performance, 2014)
Organizations are increasingly using team-based projects to achieve goals. As such, it is important to understand how team members (e.g., their differences) influence team outcomes such as effectiveness. In the present study, we examine performance diversity, differences in members` past performance, as an antecedent to team effectiveness. In addition, we assessed the length of time the group performed together as a moderator and social loafing among members as a mediator of the performance diversity—team effectiveness relationship. Using multisource data for 673 individuals in 139 project teams, we found that performance diversity had an increasingly negative effect for groups that were together longer. Specifically, greater diversity resulted in more social loafing, thereby diminishing team satisfaction and supervisor-rated team performance